Molecular Modeling of Metalloreductase STEAP2 Protein and Docking Interaction Studies: An In Silico Study: Molecular Modeling of Metalloreductase STEAP2 Protein and Docking Interaction Studies: An In Silico Study - Gunda, Shravan Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
This gene is an individual from the STEAP family and encodes a multipass film protein that confines to the Golgi complex, the plasma layer, and the vesicular cylindrical structures in the cytosol. A very comparative protein in mouse has both ferrireductase and cupric reductase action and invigorates the cell take-up of both iron and copper in vitro. Expanded transcriptional articulation of the human quality is related with prostate malignant growth movement. Substitute transcriptional graft variations, encoding distinctive isoforms, have been described. Therefore, in the present study, we generated a precise three-dimensional (3D) model of metalloreductase STEAP2 protein using MODELLER 9.21 and validated its structure using PROCHECK software. Modeled protein contains more than 94.5% of amino acids in core region. We interpreted the action of natural compounds docking against the modeled metalloreductase STEAP2 protein. Three compounds (ginkgetin, medicagenin, and erybraedin A) showed lower binding affinity values toward metalloreductase STEAP2 protein compared to mitoxantrone, abiraterone acetate, apalutamide, enzalutamide, and flutamide. Ginkgetin exhibited the lowest binding energy of âˆ’9.10 kcal/mol with interacting Trp212 and Thr210. All the 17 compounds showed excellent binding energies than standard drugs for the modeled metalloreductase STEAP2 protein. These computational studies can be helpful to discover novel drug candidates.